Bending and free vibration analysis of symmetric and unsymmetric functionally graded CNT reinforced sandwich beams containing softcore. (January 2022) - Garg, A.; Chalak, H.D.; Zenkour, A.M.; Belarbi, M.-O.; Sahoo, R.
Abstract: In the present work, bending and free vibration analyses of functionally graded carbon nanotube-reinforced (FG-CNTR) sandwich beams are carried out using finite element-based higher-order zigzag theory. Face sheets are assumed to be made up of FG-CNTR composite, and the core is assumed to be made up of balsa wood (softcore). The present formulation also takes into account transverse normal stresses. The computational model incorporates transverse shear stress and transverse normal stress continuity condition at interfaces. Zero transverse shear stress condition at the bottom and top surfaces of the beam is also satisfied. The principle of minimum potential energy is employed for carrying out bending analysis, while Hamilton's principle is adopted for free vibration analysis. The investigation is carried out for different gradation laws which govern the distribution of CNTs across the thickness of face sheets. The influence of the core's thickness on stresses and displacements is also critically analyzed in the present work. It has been observed that the thickness of the core and CNT gradation law significantly affect the mechanical behavior of the sandwich FG-CNTRC beam. Highlights: Bending and free vibration analysis of the FG-CNTR sandwich beam is carried. Face sheets are assumed to be made up of an FG-CNTR composite with a soft core. The present formulation also takes into account transverse normal stresses. The influence of the core's thickness on stresses and displacements is presented. The thickness of core and CNT gradation are widely affected the behavior of the sandwich FG-CNTRC beam.